Филогенетические взаимосвязи между Pinus sylvestris L., Pinus kochiana Klotzsh ex C. Koch и Pinus mugo Turra по данным изоферментного анализа - Коршиков, И.И.; Пирко, Я.В.; Горлова, Е.М.; Чемерис, Е.В. (Промышленная ботаника, 2002)
Phylogenetic links between Pinus sylvestris L., Pinus kochiana Klotzsh ex C. Koch and Pinus mugo Turra have been studied using the data of 9 gene-enzyme systems isozyme analysis. 11–20 trees has been sampled from 3 natural populations of these species: P. mugo – in the Ukrainian Carpathians, P. sylvestris — in Kharkov district, P. kochiana – in the Mountaineous Crimea have been employed in the investigations. Genetic structure of P. sylvestris and P. kochiana have been found to be more close, than those of P. sylvestris and P. mugo. M. Ney’s genetic distance between the species under study varied within the ranges of 0,043 to 0,114.